Psychological interventions for carers of people with dementia: A systematic review of quantitative and qualitative evidence. Issue 2 (3rd June 2013) - Elvish, Ruth; Lever, Sammi-Jo; Johnstone, Jodie; Cawley, Rosanne; Keady, John
Abstract: Rationale : Carers of people with dementia experience significant levels of stress in their everyday role. The National Dementia Strategy in England identifies the key role that carers play in supporting people with dementia living at home, often to the detriment of their social, emotional and physical health. Aims : To add to the substantive knowledge‐base by combining search criteria used by Pinquart and Sörensen (2006) and Gallagher‐Thompson and Coon (2007) to update the literature on psychological interventions for carers of people with dementia published between 2005 and 2011. Method : Following the study inclusion criteria, comprehensive searches were conducted using the electronic databases Medline, PsycINFO, ERIC, and PubMed. Twenty studies were identified, graded and synthesised into the reported systematic review with both quantitative and qualitative studies included to maximise practice application. Results : Consistent with previous findings, three categories of psychological intervention were identified: (i) psychoeducational‐skill building ( n =8); (ii) psychotherapy‐counselling ( n =1); (iii) multicomponent ( n =6). Our review also identified a fourth intervention category, (iv) technology‐based ( n =5). The majority of studies in the updated review examine the constructs of depression, burden, social support and well‐being. The development of focused interventions for carers, whether individually tailored interventions or group interventions around a common issue, was significant for developing practice. Future studies across all categories should continue to embed supervision arrangements within their psychological intervention protocols.